Natural Bioactive New Withanolides - Xu, Qian-Qian; Wang, Kui-Wu (Mini Reviews in Medicinal Chemistry, 2020)
Withanolides are a group of highly oxygenated steroids derived from a C28 ergostane skeleton, and have attracted significant scientific interest due to their complex structural features and multiple bioactivities. More than 170 new natural withanolides were isolated and identified in the last 5 years. This review provides a comprehensive summary of the structural, biological and pharmacological activities of these new compounds.
Keywords: antistress